A survey of chloramphenicol residues in aquatic products of Shenzhen, South China. Issue 6 (3rd June 2021) - Luo, Lan; Lu, Shaoyou; Huang, Chengpeng; Wang, Fu; Ren, Yan; Cao, He; Lin, Qihui; Tan, Zhiqiang; Wen, Xiaodong
ABSTRACT: Food safety is a top priority of concern for consumers. To promote growth, as well as to treat diseases which occur in aquaculture, antibiotics, even banned veterinary antibiotics, are widely used. This survey investigated the levels of chloramphenicol (CAP) by LC-MS/MS in 291 aquatic samples (all the products in this survey were local sales, exported products were not included), including shellfish, shrimp and fish, from Shenzhen, South China. The CAP concentrations in these samples (based on wet weight) were: shellfish (<LOD-205 µg kg −1, mean: 68.8 µg kg −1 ); shrimp (<LOD-2.2 µg kg −1, mean: 0.5 µg kg −1 ) and fish (<LOD-1.9 µg kg −1, mean: 0.7 µg kg −1 ). The highest concentration of CAP was found in shellfish samples ( Mactra veneriformis, 205 µg kg −1 ), these levels were greater than those reported in aquatic products from other locations in China. The detection rate of CAP was 37.2% in shellfish samples (64/172), 13.6% in shrimp samples (3/22) and 16.5% in fish samples (16/97). The detection rate of CAP in shellfish samples was higher than that in fish and shrimp samples, and therefore food safety in this region cannot be ignored. The results obtained from the current study indicated a high incidence of CAP in aquatic products in this region and argue for stronger market supervision and regulation in China. Graphical Abstract: uf0001